Pengelolaan Lingkungan Pesisir Melalui Gerakan Bersih Pantai Di Pantai Ujung Betok Pemongkong, Jerowaru, Lombok Timur - Dwiyanti, Septiana; Asri, Yuliana; Alim, Sahrul; Diamahesa, Wastu Ayu; Affandi, Rangga Idris; Diniariwisan, Damai; Rahmadani, Thoy Batun Citra; Muahiddah, Nuri; Sumsanto, Muhammad (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
ABSTRAK Coastal environmental management has an important role in maintaining balance in terms of ecology, economy and society which is a source of life for coastal communities. Coastal areas often face pressure due to human activities in the form of environmental pollution which causes indiscriminate waste disposal and ecosystem degradation. Pemongkong Village, Jerowaru District, which is one of the coastal areas of East Lombok, has beaches including Ujung Betook Beach which is one of the environmental assets and sources of livelihood, both through the aquaculture, capture and tourism sectors. The problem of waste in coastal areas is increasing due to human activities, lack of good waste management, and minimal awareness of the importance of maintaining coastal cleanliness. One solution in managing the coastal environment is through a beach cleanup movement. Beach cleanup activities in several coastal areas show increasing concern and community participation in maintaining the coastal environment. This movement not only aims to clean up waste, but also to raise public awareness of the importance of maintaining coastal sustainability. This community service activity has two stages, namely the preparation stage and the implementation stage of the beach cleanup movement. The implementation stage in this activity uses a participation method. The community service activity went smoothly. Participants in this service consisted of all elements of the Ujung Betok community, ranging from children to adults. The waste found in this activity can be classified into three types, namely waste from coastal community activities, waste left by tourists, and natural waste such as tree branches. The majority of waste found from the three types of waste is inorganic waste in the form of plastic waste. Education related to types of waste and waste management is also provided as information and knowledge. The conclusion that can be drawn from this community service activity is that the community service activity went smoothly according to plan and information related to coastal management through the Ujung Betok beach cleanup movement has been received enthusiastically by participants.